2021
DOI: 10.3389/feart.2021.734802
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Historical (1750–2020) Mass Balance of Bordu, Kara-Batkak and Sary-Tor Glaciers in the Inner Tien Shan, Kyrgyzstan

Abstract: The mean specific mass balance of a glacier represents the direct link between a glacier and the local climate. Hence, it is intensively monitored throughout the world. In the Kyrgyz Tien Shan, glaciers are of crucial importance with regard to water supply for the surrounding areas. It is therefore essential to know how these glaciers behave due to climate change and how they will evolve in the future. In the Soviet era, multiple glaciological monitoring programs were initiated but these were abandoned in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 67 publications
(117 reference statements)
0
5
0
Order By: Relevance
“…Similarly, their results suggest more positive mass balance at the beginning of the 20th century followed by increasingly negative mass balances, especially from the 1970s onward. In contrast with the here present study, Van Tricht et al [43] adjusted not only the glacier area but also the thickness over the study period. They showed that initial geometry and considerations for the glacier retreat had a strong influence on glacier mass balance.…”
Section: Comparison With Other Mass Balance Estimates For Tien Shan A...mentioning
confidence: 57%
See 3 more Smart Citations
“…Similarly, their results suggest more positive mass balance at the beginning of the 20th century followed by increasingly negative mass balances, especially from the 1970s onward. In contrast with the here present study, Van Tricht et al [43] adjusted not only the glacier area but also the thickness over the study period. They showed that initial geometry and considerations for the glacier retreat had a strong influence on glacier mass balance.…”
Section: Comparison With Other Mass Balance Estimates For Tien Shan A...mentioning
confidence: 57%
“…100 −1 m from 1985 to 1989 [42]. Van Tricht et al [43] found the average mass balance gradient from the Little Ice Age to present to span from 0.50 and 0.60 m w.e. 100 −1 m for glaciers Karabatkak, Sary-Tor, and Bordu.…”
Section: Changes In Mass Balance Gradientmentioning
confidence: 99%
See 2 more Smart Citations
“…and 0.6 m w.e. yr -1 per 100 m (van Tricht et al, 2021), in the ablation zone of glacier No.354 it was estimated as 0.68 m w.e. yr -1 per 100 m (Kronenberg et al, 2016) and for south-faced Grigoriev glacier it was 0.6 m w.e.…”
Section: Discussionmentioning
confidence: 98%